Blood canticle - Rice,Anne (New York Ballantine Books, 2003)
Continues the crossover events of "Blackwood Farm," pitting the vampire Lestat against the ghost of Julian Mayfair, who is out to evenge the transformation of Mona Mayfair, and chronicling Rowan Mayfair's dangerous attraction to Lestat.
Keywords: Anne Rice -- Blood canticle -- Fiction -- Vampires -- Lestat (Vampire), 1760-